KAITAN FIRM SIZE, PROFITABILITY, DAN LIQUIDITY TERHADAP CAPITAL STRUCTURE - Yudith, Vivi Odella; Dermawan, Elizabeth Sugiarto (Jurnal Paradigma Akuntansi, 2025)
The purpose of this study is to determine the relationship between firm size, profitability and liquidity to capital structure on consumer non-cyclical goods sector companies listed in the Indonesia Stock Exchange in 2019-2021 where the data used is secondary data in the form of company financial reports that can be obtained from the Indonesian Stock Exchange website. Using purposive sampling methods, 72 companies were obtained with 216 data can be used. This study used Spearman Rank Correlation Test with SPSS 26. The results of this study show that firm size has a weak, positive, and not significant correlation to capital structure, profitability has a fairly negative and significant correlation to capital structure and liquidity has a strong, negative and significant correlation to capital structure.